1999
DOI: 10.1103/physrevlett.83.4943
|View full text |Cite
|
Sign up to set email alerts
|

Search for Neutral Heavy Leptons in a High-Energy Neutrino Beam

Abstract: A search for neutral heavy leptons (NHLs) has been performed using an instrumented decay channel at the NuTeV (E-815) experiment at Fermilab. The decay channel was composed of helium bags interspersed with drift chambers, and was used in conjunction with the NuTeV neutrino detector to search for NHL decays. The data were examined for NHLs decaying into muonic final states (µµν, µeν, µπ, and µρ); no evidence has been found for NHLs in the 0.25 -2.0 GeV mass range. This analysis places limits on the mixing of NH… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
151
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(156 citation statements)
references
References 15 publications
3
151
0
Order By: Relevance
“…[71,72,76,81]), Fig. 6a provides an approximate drawing of the regions excluded by these constraints (depicted as shaded areas), in particular nonunitarity bounds, kaon and pion peak searches, kaon decay searches by the PS191 experiment, D meson decay searches by the CHARM [67] and NuTeV [68] experiments 13 , Z decay searches by the Delphi experiment [69], and Higgs decays data from LHC. The exclusion lines for the mixing parameter |Σ i U eN i U * µN i | are valid at 90% CL, for the present (continuous curves) and future (dashed curves) reach of the three types of measurements under discussion: µ → eγ, µ → eee and µ → e conversion.…”
Section: Minimum Seesaw Scales That Future Experiments Could Probementioning
confidence: 99%
See 1 more Smart Citation
“…[71,72,76,81]), Fig. 6a provides an approximate drawing of the regions excluded by these constraints (depicted as shaded areas), in particular nonunitarity bounds, kaon and pion peak searches, kaon decay searches by the PS191 experiment, D meson decay searches by the CHARM [67] and NuTeV [68] experiments 13 , Z decay searches by the Delphi experiment [69], and Higgs decays data from LHC. The exclusion lines for the mixing parameter |Σ i U eN i U * µN i | are valid at 90% CL, for the present (continuous curves) and future (dashed curves) reach of the three types of measurements under discussion: µ → eγ, µ → eee and µ → e conversion.…”
Section: Minimum Seesaw Scales That Future Experiments Could Probementioning
confidence: 99%
“…Their non observation sets very strong constraints in the range 1 MeV< m N < 2 GeV [65][66][67][68]. Similarly searches for a Z → N i ν decay sets interesting constraints below the M Z mass [69].…”
Section: Minimum Seesaw Scales That Future Experiments Could Probementioning
confidence: 99%
“…2 [8,[25][26][27][28][29][30][31][32][33][34][35][36][37][38], with the least explored parameter space being M N > m b . The proposed SHiP [39] and DUNE/LBNF experiments [40] are expected to greatly improve sensitivity for N below 1 A recent review of the collider phenomenology of RH neutrinos can be found in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Accelerator-based experiments probe the mass range MeV-TeV depending on the center-of-mass energy available and the process investigated [28][29][30][31][32], just to mention some examples. Additionally, global analyses have investigated the parameter space of the active-sterile mixing in the GeV-TeV range by the use of electroweak (EW) precision observables [33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%